Socio-spatial lifestyles and segregation - Schnell Izhak (Cybergeo, 1999)
The paper suggests an alternative index for socio-spatial segregation which emphasises agents’ segregation in everyday life. We argue that segregation should be studied for individual agents in respect to the spaces in which they perform their everyday life. The index refers both to the spatial and the social-interactive contexts of seven aspects (home, cluster of neighbouring homes, neighbourhood and city in the spatial context and friends, work and leisure activities in the social context) of agents’ everyday life actions as they are actually performed in their everyday time-spaces. The paper calculates the segregation of seven persons who represent seven typical lifestyles. Each lifestyle differs in its preferences for location in social spaces and in performing everyday life activity orbits.The index may receive negative values representing agents’ tendency toward exposure to members of alternative groups and positive values representing tendency toward segregation. In practice, the distribution of the segregation index changed between +- 4.0. In addition, no correlation between spatial and social segregation has been identified. Several agents were socially much more segregated than spatially, while others were spatially more segregated than socially.